Morals, Adab, and Morale in the Context Education Islam Contemporary - Imroatuz Zahra Ramdhani; Husnul Chotimah; Nihla Zanjabila; Aura Nayla Ardya; Adzkiya Syifa Az-zahro; Moch Mahdiyan Nasikhin (Civiliza Publishing, Indonesia., 2026)
The crisis of morals and manners that hit the young generation of Muslims in the digital era is the main background of this research. The moral degradation that is seen through bullying behavior, the weakening of social ethics, and the loss of respect for teachers show the need to strengthen the concept of character in Islamic education. This research aims to examine in depth the concepts of morals, manners, and morals in the context of contemporary Islamic education and explore their implications for the formation of an ethical and characterful learning environment. The research uses a qualitative approach with a library research method which is strengthened by normative-philosophical analysis of the sources of the Qur'an, Hadith, as well as the thought of classical and contemporary scholars such as Al-Ghazali, Ibn Miskawaih, and Syed Muhammad Naquib Al-Attas. The results of the study show that morality, manners, and morals are three concepts that complement each other: morality as an inner foundation, adab as an expression of behavior, and morals as social standards. The concept of ta'dib Al-Attas has proven to be the most comprehensive framework of Islamic education because it integrates the formation of knowledge, character, and manners in an integrated manner. Its implementation through a morality-based curriculum, teacher examples, and the integration of Islamic values in learning have proven to be effective in forming a generation of Muslims with integrity. It is concluded that the revitalization of adab values in Islamic education is a strategic imperative to answer the challenges of globalization and moral crises. Empirically advanced research in various Islamic educational institutions is highly recommended.